Alvenaria estrutural: construindo conhecimento - Machado, Diego Willian Nascimento (2015)
Innovations in building systems over the years have raised the masonry, through large and important works built in the past, allowing the understanding of logic and design of the elements and materials used, as well as its constructive process. The aim of this is to research on the technological process of structural masonry in the course of human history and present it through the project-book called, Structural Masonry: Building Knowledge. With the following objectives: to propose the organization and sequencing for the structural masonry education; provide an overview of the technical principles for the design of architectural design; demonstrate the correlation between technical and adopted system, addressing the advantages and disadvantages to the system, linked to performance quality; and propose equipment designed for architects, engineers and technicians in buildings with didactic, based on a graphical tool. The research methodology is divided into two stages: the first exploratory, from a literature review to determine the basics of building system. The second stage consists of the construction of so-called project-book, Structural Masonry: Building knowledge, grounded in theory the initial research and the use of graphics resources devoted to visual understanding of the system. As a result, the book obtained is developed in chapter 4: Chapter 1 - Historical aspects; Chapter 2 - Materials: Components and elements; Chapter 3 - Project Structural Masonry; and Chapter 4 - Execution of works Structural Masonry. Completing the dissertation is observed that the project-book in question is regarded as an introductory teaching resource to the system in Structural Masonry. Therefore, seeks its verbal content in a clear and clean arrangement, which scored well parts that should be highlighted, bringing dynamism and interactivity to the reader. The continuity in evaluating the use of the book in educational institutions become necessary for insertion of the same in the social context be it under construction, universities, teaching methods, design, and so on.